Supporting food security through urban home gardening, Rancasari Sub-district, Bandung City, West Java, Indonesia - INDRI WULANDARI; TEGUH HUSODO; DEDE MULYANTO; OEKAN S. ABDOELLAH; CIKA ASTI AMALIA; SHOFI SITI FARHANIAH (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Wulandari I, Husodo T, Mulyanto D, Abdoellah OS, Amalia CA, Farhaniah S. 2023. Supporting food security through urban home gardening, Rancasari Sub-district, Bandung City, West Java, Indonesia. Biodiversitas 24: 5618-5625. Urban areas are closely related to the increase in human population, which triggers increased demand for land for settlements or housing. The increase in human population is in line with the increase in daily food requirements. As agricultural land decreases, agricultural productivity decreases, but much agricultural land has been converted into non-agricultural land, leading to food insecurity. Urban farming through home gardening is one of the methods to maintain food security amidst limited open land. This study aimed to reveal urban farming as a role model for food security through home gardens in the Rancasari Sub-district, Bandung City, West Java, Indonesia. This study used a quantitative approach. Data were collected using purposive sampling in housing >20 years old in Manjahlega and Mekarjaya Village. Plants are divided based on their utilization, including ornamental, spice, medicine, and food plants. The results showed that 803 species and 20,366 individuals of 130 families were found in Manjahlega Village, while 680 species and 10,862 individuals were found in the Mekarjaya Village. In Manjahlega, mango (Mangifera indica L.) has the highest IVI value of 64.58, while in Mekarjaya, Chinese evergreen (Aglaonema commutatum Schott.) has the highest IVI value of 10.2. Based on their use, ornamental plants have the highest H and R values compared to food, medicines, and spice plants. Ornamental plants dominate home gardens in Rancasari Sub-district. Their home gardens tend to be aimed at providing aesthetic value and beauty rather than producing food, medicines, and spices in the household. Home gardening has not been fully effective in supporting urban farming in Rancasari Sub-district due to the selection of ornamental plants.